Are Neuromuscular Disorders That Cause Fatigue a Contraindication to Sports Participation? A Case Report and Narrative Review of the Literature - Marianna Papadopoulou; Maria Ioanna Stefanou; Dimitrios Stasinopoulos; Vasiliki Zouvelou; George Papadimas; Christos Moschovos; Pinelopi Vlotinou; Elisabeth Chroni; Georgios Tsivgoulis (Applied Sciences)
Engaging in sports, particularly at a competitive level, requires sustained muscle contractions before the onset of physical fatigue. Fatigue is highly prevalent in neuromuscular diseases, especially those affecting neuromuscular transmission (e.g., myasthenia gravis) or muscle membrane excitability (e.g., myotonia, certain metabolic myopathies). A decremental response in repetitive nerve stimulation (RNS) represents the neurophysiological analogue of exercise-induced muscle weakness. Patients with such responses exhibit abnormal suppression of muscle activity during repetitive or prolonged effort. Consequently, it is often assumed they should avoid strenuous physical activity. To assess the safety of sports participation in individuals with fatigability-related neuromuscular disorders, we examined the literature and report a new case of a patient with myotonia congenita who engaged in competitive sports without adverse events. The review identified only a few cases involving patients with myasthenia gravis or muscular dystrophies who also participated in competitive sports safely and with favorable outcomes. No adverse events were reported. While these findings suggest that sports participation may be feasible for selected patients, they cannot be generalized. Large-scale studies involving athletes with neuromuscular conditions are needed to evaluate the safety and long-term impact of exercise in these populations.